The Taxonomy of Thinking in Reading Questions in “Look Ahead an English Course for Senior High School Level 1, 2, & 3” - Beny Septian Panjaitan and Rahmad Husein (REGISTER: Journal of English Language Teaching of FBS-Unimed, 2017)
This study aimed at analyzing the cognitive dimension based on Revised BloomTaxonomy in reading questions in Look Ahead an English Course for Senior HighSchool Level 1, 2, & 3. This study used quantitative research design. The sampleswere 141 reading questions which taken by using random sampling technique byusing Statistical Program for Social Science (SPSS) version 20.0. in Look Aheadan English Course for Senior High School Level 1, 2, & 3. The data were analyzedby using Table analysis of cognitive dimension of Revised Bloom Taxonomy. Theanalysis showed that the most dominant cognitive dimension of Revised BloomTaxonomy in remembering dimension (57.45%). The second dominant cognitivedimension is understanding dimension (26.24%). The third dominant cognitivedimension is evaluating dimension (10.64%). The fourth dominant cognitivedimension is creating dimension (3.55%). The fifth dominant cognitive dimension isanalyzing dimension (2.13%). There was no cognitive dimension of applyingdimension that applied in reading question of the textbooks.